PENGGUNAAN GRAPH BASED METHOD DAN SOFTWARE BLOCPLAN UNTUK MEMPEROLEH LAYOUT YANG OPTIMAL DI DEPT. ACOUSTIC GUITAR PT. YMMI - Sulasmana Nur (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2025)
YMMI is a manufacturing company engaged in the manufacture of acoustic and electric guitars. In the production flow, the average material handling distance in the Acoustic Guitar department (16,1m) is greater than that of Electric Guitar (12.7m), this causes a difference in the material handling cost of the Acoustic Guitar and Electric Guitar departments, where the material handling cost of the Acoustic Guitar department is Rp. 495.334, and Electric Guitar amounting to Rp. 350.918. The distance shift, especially in the Top Coating – Finishing workstation with a distance of 44.6m and SR Top Coating – Finishing with a distance of 48.3m, makes the high cost of material handling in the Acoustic Guitar department. The results of the Graph Based Method obtained the calculation of OMH/Day of Rp. 431.622, and the proposal of Blocplan Software of Rp. 373.085. The minimum material movement distance was chosen, namely the Blocplan Software layout proposal, with a percentage reduction in the total displacement distance of 20% calculated using the Rectilinear method calculation, as well as a reduction in material handling costs by 25%.